Chronicling the effect of COVID-19 on orthopedic literature - Liu, Ivan Z. (J Orthop, 2021)
BACKGROUND: The novel coronavirus disease (COVID-19) has had a significant impact on orthopedic surgery practice, but there has been little investigation of the effects of COVID-19 on the orthopedic surgery literature. Additionally, because orthopedic research plays a vital role in physician education, changes to the characteristics and content of published literature can have lasting impacts on future teaching and learning. This paper represents the first known analysis of the COVID-19 pandemic's impact on peer-reviewed articles published in orthopedic surgery journals. METHODS: The 20 orthopedic journals with the highest impact factors in 2019, according to the Journal Citation Reports, were included in this study. Using PubMed and COVID-19 related keywords as well as manual screening, a final count of 199 articles were assessed for this study and subsequently sorted by country of origin, orthopedic subspecialty, article type, and general theme. Kruskal Wallis and Pearson's Chi-squared tests were used to analyze continuous and categorical variables, respectively. RESULTS: Fourteen journals published articles relating to COVID-19, representing 26 countries with the United States (37%) and United Kingdom (13%) publishing the greatest proportion of all COVID-19 articles. Sixty percent of publications discussed COVID-19's impact on the overall field of orthopedic surgery, with the remainder focusing on specific subspecialties. Forty-seven percent of publications were original research articles while 46% were editorials or commentaries. The median time to publication for all COVID-19 related articles was 24.5 days, compared to the 129 days reported for orthopedic journals prior to the COVID-19 pandemic (p < 0.001). In the first 100 articles published, 49% (n = 49) originated exclusively from United States institutions, whereas only 25% (n = 25) of the next ninety-nine articles had US-only institutions (p < 0.001). CONCLUSIONS: The COVID-19 pandemic has significantly impacted the characteristics, content, and time to publication of the orthopedic surgery literature. The data and ideas presented in this paper should help streamline future, formal analysis on the lasting implications of COVID-19 on orthopedic surgery practice, teaching, and learning.